Analisis Activity Rasio Pada Sektor Informal di UMKM kuliner di Kota Palangka Raya - Sumarianto Sumarianto; Dicky Perwira Ompusunggu; Kristi Damayanti G; Dede Salwa Oktavia; Niko Pasaribu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to evaluate the financial and operational conditions of culinary MSMEs in Palangka Raya City using activity ratio analysis, as well as formulating strategies to increase their efficiency and competitiveness. This analysis uses data on initial capital, income and costs of various types of snacks in Palangka Raya City which were collected through interviews and field observations. Sellers of snacks such as satay, POP Ice drinks, jasuke, cassava chips and boiled peanuts provide detailed information about their capital, daily income and operational costs. The data is analyzed using the activity ratio formula to assess operational efficiency and identify the strengths and weaknesses of each business, providing insight for traders to increase profitability. The results of this research show that the activity ratios, namely Turnover Asset Ratio (TAT) and Inventory Turnover (IT), in various types of culinary MSMEs in Palangka Raya City are relatively similar. The effectiveness of asset use and inventory management for traditional snack businesses shows the same pattern. These findings emphasize the importance of increasing operational efficiency and asset management for culinary MSMEs. However, this research has limitations in sample size and area coverage, so further research with a larger sample and wider area is needed to provide a more comprehensive picture.